A Psychological Study on Gender and Emotional Wellbeing of Indian Research Scholars: A Phenomenological Comparison - Bajaj, Neema (International Journal of Psychosocial Rehabilitation, 2020)
The role of gender differences with respect to emotional wellbeing, general health, adjustment level and psychopathological status of Indian Ph.D. research scholars was investigated, in the year 2008-2009. The sample consisted of 60 Ph.D. research scholars (30 males and 30 females), aged between 24-29 years, who volunteered for the study. The research was divided into two phases. First, the quantitative phase involved the administration of four self report psychometric measures namely, General Health Questionnaire, PGI General Wellbeing Measure, Adjustment Inventory for College Students and Symptom - Checklist – 90 –R. Secondly, the qualitative phase involved a follow-up semi-structured interview with 10 male and 10 female subjects, who volunteered for the interview. Interview was used to explore the phenomenological experiences of subjects and was discussed in terms of understanding various themes. One-way analysis of variance was employed to see if any significant gender differences existed. Based on psychometric testing (Mean, Standard Deviation and One- way ANOVA), no significant gender differences in the emotional wellbeing, general health and adjustment level of research scholars were found. However, significant gender differences existed on the symptom dimensions of somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation and psychoticism. Females displayed more psychological distress pertaining to their subjective experiences. The study completed in April,2009.